PUTUSAN HAKIM TERHADAP PERKARA GHAIB PADA CERAI GUGAT DI PENGADILAN AGAMA METRO - Ulfa Fatimatu Zahra; Sudirman (SAMAWA, 2026)
This study analyzes the judge's consideration in deciding supernatural cases in divorce lawsuits at the Metro Religious Court through Decision Number 230/Pdt.G/2023/PA.Mt. The main problem is how the judge decides the supernatural divorce case when the husband leaves his wife for less than two years, even though Article 116 letter (b) of the KHI requires a minimum of two consecutive years. Using normative legal research methods with a legislative and case approach, this study analyzes court decisions and Islamic legal literature. The results of the study show that judges use a substantive-protective approach by integrating legal-formal and philosophical aspects based on the rules of fiqhiyyah "dar'u al-mafasid muqaddamun 'ala jalb al-mashalih" and the principles of maqashid sharia. Factors that cause the request include the absence of the husband, economic neglect, the habit of drinking liquor, and the failure of peace efforts. The judge granted the lawsuit by imposing talaq satu ba'in shughra even though the duration of the separation had not reached two years, considering that maintaining the marriage caused psychological harm and legal uncertainty for the wife. This study demonstrates that judges act as justice seekers who contextualize legal norms with social realities to protect the abandoned party. Keywords: Supernatural Cases, Divorce Lawsuits, Judge's Considerations